Práticas discursivas intersemióticas: dos tópicos semantizadores à construção de sentidos em textos multimodais de gêneros digitais - Oldoni, Cristiano (2020)
The presented research which the name is Texts and images on the scene: the sense in multimodal genres. The theme of this is study is the discursive multimodality and its delimitation is the construction of the meaning in texts with multimodal genres, analyzing the "enunciation scene", "set design". The objective of this study is to analyze how the meaning of these texts that are part of the Portuguese textbooks of the High School, are produced from the analytical reconstruction of its "enunciation scene" and its "scenery", considering the contributions of Maingueneau (2008a, 2008b, 2010), when it comes to the text plan of making discursive practice. Through this objective the theoretical background is basically connected to the studies about discursive textual genres of Bakhtin (2011), Marcuschi (2002), Rojo (2007) and Schneuwly and Dolz (2007); when it comes to the reading practice there are Chartier (1994) and Petit (2008); Dionísio (2011) about multimodality; Rojo (2012) alluding the multiliteracies; Benveniste (1976, 2006a) and his contributions that are related to the (inter) subjectivity in language and the formal framework of the language realization; Benveniste (2006b) e Maingueneau (2008c), when it comes to the intersemioses and Maingueneau (2008a, 2008b, 2008d, 2010) about the Discourse Analysis. To enable the possibility of global analysis of the multimodal texts, we suggest a specific methodological device for seizure the discursive occurrences of senses of this nature. The corpus, is compound by three texts from the High School textbook which the title is: “Português – Linguagens”, written by Cereja e Magalhães (2010). We applied this device to demonstrate its productivity. We selected the High School level because on this stage of the Basic Education, the multimodal texts deserve a didatic treatment with discursive enunciative approach. Thus, the global meaning will make sense. The selection of the textbook occurred mainly because it is the material with the highest rate when it comes to its adoption in the country, according to the data released by MEC. The research has a qualitative and partly quantitative approach, with applied nature. When it comes to the objective, it is exploratory-descriptive; the technical procedure involves bibliographical and documentary research. We have as our general result of our studies a scenery closer to the discursive reality, in a technical, theoretical and didatic level. We believe that this research will contribute as well to the strengthening of academic knowledge as to the didactic and pedagogical methods which the interests are connected to the notions of gender, critical reading and projection / construction of meaning of the texts that use the discursive multimodality.